PERANCANGAN FASILITAS WISATA SPIRITUAL BERBASIS PELESTARIAN BUDAYA - Prajnawrdhi, T.A.; Paramadhyaksa, I.N.W.; Mahastuti, N.M.M.; Satria, M.W. (Buletin Udayana Mengabdi, 2024)
Pedawa Village, as one of the indigenous Bali Mula villages located in Banjar District, Buleleng Regency which has been designated as one of the new tourist destination villages in Buleleng Regency. The village is developing itself as a viable tourist destination. Spiritual tourism design is one type of tourism facility that is planned in the tourist village master plan in Pedawa Village. The planned spiritual tourism facilities are facilities that are able to accommodate all spiritual activities such as: meditation, healing/healing, yoga, holy baths (melukat), religious rituals during traditional ceremonies/prayer, learning about the cultural and historical traditions of Pedawa village such as traditional dances; folk games; language; culinary; and sacred offerings. Through planning this spiritual tourism facility, Pedawa village will be ready to become a tourist village and accept tourists who will participate in spiritual tourism. Comprehensive field observations and interviews are used to obtain accurate data that will be used as a basis for planning. The result shows that design drawing is in the form of a site plan of spiritual tourism facilities, as well as details of the design of each main and supporting building that is planned to be the basis for the development of this area. This facility planning is also in an effort to optimize local culture as the basis of tourism development and at the same time conserve local wisdom in Pedawa village. Keywords: culture, Pedawa, conservation, spiritual, tourism.